(untitled) (Revista da EGN, 2025)
This article is situated within Geopolitics and Strategic Studies, addressing a gap in Brazilian literature on the geopolitical concept of the Blue Homeland (Mavi Vatan). This concept underpins Turkey’s naval strategy and is rooted in its strategic rivalry with Greece, especially regarding sovereignty and energy resource exploration. The objective was to define the theoretical variable “Blue Homeland,” reflecting Turkey’s perspective on its surrounding seas: the Mediterranean, Aegean, and Black Seas. This definition aimed to understand naval strategy behaviour in these maritime spaces. A Case Study methodology, supported by historical and experimental methods, was used. The findings indicate that the Blue Homeland concept, developed in 2006, was adopted by the Turkish Navy’s strategic framework by 2020. It is seen as a form of neo-Ottomanism, seeking to restore Turkey’s historic role as a major power in the Middle East under President Erdoğan. The study concludes that the strategic logic of the Blue Homeland, amid Turkey-Greece rivalry, has driven the modernization and strengthening of Turkey’s Naval Force. Ultimately, the Blue Homeland signifies complete strategic autonomy, which is crucial for the survival of the Turkish state.